Divergent electrophysiologic action of dapagliflozin and empagliflozin on ventricular and atrial tachyarrhythmias in isolated rabbit hearts - Wolfes, Julian; Uphoff, Jan; Kemena, Sven; Wegner, Felix; Rath, Benjamin; Eckardt, Lars; Frommeyer, Gerrit; Ellermann, Christian (Frontiers in Cardiovascular Medicine, 2024)
Background The use of SGLT-2 inhibitors has revolutionized heart failure therapy. Evidence suggests a reduced incidence of ventricular and atrial arrhythmias in patients with dapagliflozin or empagliflozin treatment. It is unclear to what extent the reduced arrhythmia burden is due to direct effects of the SGLT2 inhibitors or is solely a marker of improved cardiac function. Methods One hundred five rabbit hearts were allocated to eight groups and retrogradely perfused, employing a Langendorff setup. Action potential duration at 90% of repolarization (APD90), QT intervals, effective refractory periods, conduction velocity, and dispersion of repolarization were obtained with monophasic action potential catheters. A model for tachyarrhythmias was established with the IKr blocker erythromycin for QT prolongation associated proarrhythmia as well as the potassium channel opener pinacidil for a short-QT model. An atrial fibrillation (AF) model was created with isoproterenol and acetylcholine. With increasing concentrations of both SGLT2 inhibitors, reductions in QT intervals and APD90 were observed, accompanied by a slight increase in ventricular arrhythmia episodes. During drug-induced proarrhythmia, empagliflozin succeeded in decreasing QT intervals, APD90, and VT burden whereas dapagliflozin demonstrated no significant effects. In the presence of pinacidil induced arrhythmogenicity, neither SGLT2 inhibitor had a significant impact on cardiac electrophysiology. In the AF setting, perfusion with dapagliflozin showed significant suppression of AF in the course of restitution of electrophysiological parameters whereas empagliflozin showed no significant effect on atrial fibrillation incidence. Conclusion In this model, empagliflozin and dapagliflozin demonstrated opposite antiarrhythmic properties. Empagliflozin reduced ventricular tachyarrhythmias whereas dapagliflozin showed effective suppression of atrial arrhythmias.